2024
DOI: 10.1038/s41467-023-44418-1
|View full text |Cite
|
Sign up to set email alerts
|

Resolving electron and hole transport properties in semiconductor materials by constant light-induced magneto transport

Artem Musiienko,
Fengjiu Yang,
Thomas William Gries
et al.

Abstract: The knowledge of minority and majority charge carrier properties enables controlling the performance of solar cells, transistors, detectors, sensors, and LEDs. Here, we developed the constant light induced magneto transport method which resolves electron and hole mobility, lifetime, diffusion coefficient and length, and quasi-Fermi level splitting. We demonstrate the implication of the constant light induced magneto transport for silicon and metal halide perovskite films. We resolve the transport properties of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“… Additionally, PANDI significantly suppressed surface and interface recombination by a factor of 4 (Figure f). , Furthermore, the capabilities of SAM in passivating surface and bulk defects, particularly through crystallization modification, resulted in better performance of the solar cell devices, as discussed below. The reported time constants are in agreement with trPL data in Figure S17b and previous reports for high-quality perovskite thin films. …”
supporting
confidence: 91%
“… Additionally, PANDI significantly suppressed surface and interface recombination by a factor of 4 (Figure f). , Furthermore, the capabilities of SAM in passivating surface and bulk defects, particularly through crystallization modification, resulted in better performance of the solar cell devices, as discussed below. The reported time constants are in agreement with trPL data in Figure S17b and previous reports for high-quality perovskite thin films. …”
supporting
confidence: 91%
“…Therefore, The polarity of minority and majority charge carriers plays a decisive role regarding trapping of charge carriers. CLIMAT measurements 42 showed that holes are the majority and electrons are the minority charge carriers in our 2D HaPs. The concentration of holes was very small in the dark and amounted to only about 10 9 cm −3 and increased to more than 10 11 cm −3 under illumination depending on light intensity and photon energy (see Figure 6a).…”
Section: ■ Introductionmentioning
confidence: 73%
“…To compare the difference in the self-p-doping level due to the addition of the trivalent cations, we measured the conductivity of the samples (Figure 2b), which provides a direct and effective means to deduce doping and trap density. 30 The conductivity is proportional to the concentration of the majority carrier, which in the THP case corresponds to the free hole density. 31 The observed reduction in conductivity, as evidenced in the case of ScI 3 and LaI 3 doping, aligns with the predictions from DFT calculations, indicating a decrease in selfp-doping by passivation of V Sn 2− defects.…”
mentioning
confidence: 99%
“…We also observed shift of the PL peak position toward higher energy, which according to the Burstein–Moss effect can be linked to a reduction of the hole density , and shallow trap concentration. To compare the difference in the self-p-doping level due to the addition of the trivalent cations, we measured the conductivity of the samples (Figure b), which provides a direct and effective means to deduce doping and trap density . The conductivity is proportional to the concentration of the majority carrier, which in the THP case corresponds to the free hole density .…”
mentioning
confidence: 99%